The Consumption of Advertising in the Digital Age: Attention and Ad Content - Dukes, Anthony; Liu, Qihong (Management Science, 2024)
This article studies the consumption of advertising when attention is costly. Our objective is to understand the advertiser’s optimal decision for informational and noninformational content when facing consumers with heavy distractions common in the digital age. We take an equilibrium approach in which an ad is consumed if and only if the content of the ad is worth the viewer’s attention. We classify many advertising decisions observed in practice. First, an advertiser can structure content to induce curiosity for continued viewing by showing the information that is relatively less likely to resonate with the broad audience. This tactic is evident in clickbait ads and “mystery ads.” Second, we find that digital ads, which tend to be skippable, have lower amounts of noninformational content (e.g., entertainment) relative to nonskippable ads. This finding can explain the industry perception that ads on digital media are of lower copy quality than traditional ads. This paper was accepted by Dmitri Kuksov, marketing. Funding: This work was supported by the Marketing Science Institute [Grant 4000790]. Supplemental Material: The online appendix is available at https://doi.org/10.1287/mnsc.2023.4793 .